2011
DOI: 10.2217/nnm.11.47
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Biocompatibility of DMSA-Stabilized Maghemite Magnetic Nanoparticles in Nonhuman Primates ( Cebus Spp.)

Abstract: DMSA-MNPs were preferentially distributed to the lung, liver and kidneys. Furthermore, DMSA-MNPs were considered biocompatible, supporting their application as a promising nanomaterial platform for future biomedical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 60 publications
5
31
1
Order By: Relevance
“…This implies that MNP were transformed to other non-superparamagnetic iron forms that can be processed and partially removed by iron metabolic pathways. In contrast to results from studies in which other DMSA-coated nanoparticles were used [25], we observed no DMSA-MNP in kidney, which might be due to differences in the animal model and/or physical characteristics of the nanoparticles. In addition, biodistribution might depend not only on the physicochemical properties of this type of nanoparticle, but also on extrinsic factors such as MNP dose and the type of anesthetic used [54].…”
Section: Biodistribution and Biotransformation Of Dmsa-mnp In Murine contrasting
confidence: 99%
See 1 more Smart Citation
“…This implies that MNP were transformed to other non-superparamagnetic iron forms that can be processed and partially removed by iron metabolic pathways. In contrast to results from studies in which other DMSA-coated nanoparticles were used [25], we observed no DMSA-MNP in kidney, which might be due to differences in the animal model and/or physical characteristics of the nanoparticles. In addition, biodistribution might depend not only on the physicochemical properties of this type of nanoparticle, but also on extrinsic factors such as MNP dose and the type of anesthetic used [54].…”
Section: Biodistribution and Biotransformation Of Dmsa-mnp In Murine contrasting
confidence: 99%
“…MNP biodistribution and toxicity in the body is the other main concern that arises from the increasingly widespread use of nanoparticles for biomedical applications. Several studies in animal models showed preferential accumulation of iron oxide MNP in spleen and liver, and to a lesser extent in other organs, depending on dosage and surface coating [21][22][23][24][25]. Other research showed that iron metabolism biochemical pathways can process iron oxide MNP [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…4, administration of dextran-coated Fe 3 O 4 (average diameter, 9.4 nm) caused free iron to be released and no damaged cells or any other kind of morphological alterations were reported in the tissues investigated (Lacava et al 2004). Similarly, Monge-Fuentes et al (2011) studied the biocompatibility of -Fe 2 O 3 (stabilized with DMSA; DMSA-MNPs) and reported that MNPs might be safe in non-human primates. DMSA-MNPs i.v.…”
Section: Livermentioning
confidence: 99%
“…Meso-2,3-dimercaptosuccinic acid (DMSA) has been used for surface-functionalization of bare maghemite nanoparticles at increasing surface-grafting values, revealing a rich scenario of interparticle and intra-particle linking via disulfide bridges resulting from the oxidation of neighboring thiol groups [78]. The biodistribution and biocompatibility of DMSA-coated maghemite nanoparticles have been recently tested in non-human primates [79]. DMSA-coated magnetic nanoparticles were conjugated to amine-functionalized poly-ethylene glycol (PEG) and revealed reduced internalization in cancer cell lines and extended circulation time in in vivo assays [80].…”
Section: Nanoparticle-based Hyperthermiamentioning
confidence: 99%